Determinação da doçura ideal em néctar de mamão adicionado de açúcar - Braga, Héberly Fernandes; Conti-Silva, Ana Carolina [UNESP] (FapUNIFESP (SciELO), 2014)
Papaya is a fruit whose pulp has attractive sensory, chemical and digestive characteristics, with high production in the country. Nevertheless, the nectar of this fruit is not widespread in the market. Thus, this study aimed to develop nectars of papaya with different sugar contents to adjust the sweetness to sugar ideal for this product. Four formulations of nectar of papaya were prepared with the same proportions of pulp and water, and sugar concentrations at 6, 8, 10 and 12%. One hundred untrained panelists participated to the affective test of acceptance by the justabout- right scale with nine categories, ranging from extremely less sweet than ideal to extremely sweeter than ideal. There was an increase in the percentage for the ideal sweetness as sugar concentration increased from 6 to 12%. There was also verified a predominance in the frequency of responses for the categories less sweet than ideal to nectar of papaya with 6% sugar and for the categories sweeter than ideal to nectar of papaya with 12% sugar. The sugar concentration must be 10.4% to obtain nectar papaya with ideal sweetness.
Determination of ideal sweetness in nectar of papaya with sugar
Keywords: Just-about-right scale; Sensory acceptability; Sweetness